Badass gully morphodynamics and sediment generation in Waipaoa Catchment, New Zealand. Issue 15 (13th October 2020) - Fuller, Ian C.; Strohmaier, Florian; McColl, Samuel T.; Tunnicliffe, Jon; Marden, Michael
Abstract: Large (>0.1 km 2 ) gully–mass movement complexes (badass gullies) are significant contributors to the sediment cascade in New Zealand's steepland East Coast Region catchments. The scale of change taking place in these gully systems allows significant evolution in morphology and sediment dynamics to be tracked at annual to decadal timescales. Here we document changes in two adjacent badass gullies in Waipaoa catchment (Tarndale and Mangatu) to infer sediment generation processes and connectivity using a morphological budgeting approach. A baseline dataset for this study is provided by a LiDAR‐derived digital elevation model (DEM) in 2005. We produced new DEMs and orthophoto mosaics using photogrammetry in 2017, 2018, and 2019 to quantify gully morphodynamics and associated volumes of sediment erosion and deposition in both systems as they co‐evolved. Results indicate ongoing rapid development of both gully complexes. Severe erosion took place at the gully heads with lowering and migration (up to 25 m vertically and laterally) of the topographic divide separating the two gullies between 2005 and 2019. Over the same period, net lowering of each gully system was ~250 mm year −1 . Key sediment‐generating processes included surface erosion, deep‐seated landslides, and debris flows. Longer term, the overall contribution of sediment from both badass gullies to the Waipaoa catchment has been declining. In the mid‐20th century, both gullies yielded in excess of 300 kt year −1 . From 2005 to 2019, 80 kt year −1 was yielded from Tarndale and 110 kt year −1 from Mangatu. Our most recent surveys demonstrated considerable variability in sediment yield, ranging from 76 kt year −1 (2017–2018) to 291 kt year −1 (2018–2019). The annual variability observed reflects the complex morphodynamics of discrete hillslopes and tributary fans in these badass gully systems and underlines the importance of integrating decadal and annual surveys when assessing system trajectory. © 2020 John Wiley & Sons, Ltd. Abstract : We use SfM photogrammetry and LiDAR datasets to quantify the dynamics of two head‐to‐head badass gullies. Tarndale cannibalizes Mangatu, shifting the divide by ~25 m between 2005 and 2019, which drops >20 m in this period. Significant sediment generated is stored in the fan apexes in both systems, notably Tarndale, with the remainder exported to the Waipaoa drainage network: reduced storage capacity means Mangatu is the more efficient conveyor of sediment, yielding ~1.5 Mt compared with Tarndale's ~1 Mt.